Micropatterned Silica Films with Nanohydroxyapatite for Y-TZP Implants. (August 2018) - Miranda, R.B.P.; Grenho, L.; Carvalho, A.; Fernandes, M.H.; Monteiro, F.J.; Cesar, P.F.
This investigation aimed at developing micropatterned silica thin films (MSTFs) containing nanohydroxyapatite (nano-HA) microaggregates that were not completely covered by silica so that they could directly interact with the surrounding cells. The objectives were 1) to evaluate the effect of the presence of 2 films (MSTF with or without nano-HA addition) on the characteristic strength (σ0 ) and Weibull modulus ( m ) of a yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) and 2) to evaluate the effect of these 2 films, as applied onto the Y-TZP surface, on the morphology, orientation, and proliferation of MG63 cells. Sol-gel process and soft lithography were used to apply the MSTF onto the Y-TZP specimens. Three experimental groups were produced: Y-TZP, Y-TZP + MSTF, and Y-TZP + MSTF + sprayed nano-HA. All surfaces were characterized by scanning electron microscopy and energy-dispersive X-ray spectroscopy and tested for 4-point flexural strength ( n = 30) in water at 37 °C. Weibull analysis was used to determine m and σ0 (maximum likelihood method). In vitro biological behavior was performed with human osteoblast-like cells (MG63). Y-TZP was successfully coated with MSFT and MSFT + nano-HA. Scanning electron microscopy micrographs indicated that the microaggregates of nano-HA were not entirely covered by the silica. There was no statistically significant difference among the experimental groups for σ0 and m . In the groups containing the films, the cells were elongated and aligned along the lines. The MSFT + nano-HA group showed significantly higher cell metabolic activity than that obtained for the Y-TZP group at day 7. This investigation was successful in producing an MSTF containing nano-HA microaggregates that remained exposed to the environment. The developed films did not jeopardize the structural reliability of a commercial Y-TZP, as confirmed by the Weibull statistics. The MG63 cells seeded over the films became elongated and aligned along the films' micropatterned lines. Y-TZP specimens coated with MSTF and nano-HA showed a higher cell metabolic activity and proliferation after 7 d of culture when compared with uncoated Y-TZP.